2013
DOI: 10.2166/wst.2013.750
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the performance of a natural treatment process using metagenomics for improved trace organic chemical attenuation

Abstract: By utilizing high-throughput sequencing and metagenomics, this study revealed how the microbial community characteristics including composition, diversity, as well as functional genes in managed aquifer recharge (MAR) systems can be tuned to enhance removal of trace organic chemicals of emerging concern (CECs). Increasing the humic content of the primary substrate resulted in higher microbial diversity. Lower concentrations and a higher humic content of the primary substrate promoted the attenuation of biodegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Given these limitations along with the increasing accessibility of high-throughput sequencing and mass spectrometry techniques, there is growing interest in using molecular data generated via meta-omics methodologies (i.e., methodologies that attempt to characterize the complete set of genes, transcripts, or enzymes of a community) to elucidate causal associations with biotransformations. [16][17][18][19][20] The general strategy is to isolate and characterize aggregate DNA, RNA, or proteins from in situ environmental communities and use the abundances of genes or gene products to establish associations that reflect the communities' potential for biotransforming one or more contaminants (referred to here as a meta-omics association study). In this context, we use the term "association" to refer to a statistical relationship between two variables, which may be described quantitatively (e.g., a linear or monotonic relationship) or qualitatively (e.g., a co-occurrence relationship).…”
Section: Why Use Meta-omics Association Studies?mentioning
confidence: 99%
“…Given these limitations along with the increasing accessibility of high-throughput sequencing and mass spectrometry techniques, there is growing interest in using molecular data generated via meta-omics methodologies (i.e., methodologies that attempt to characterize the complete set of genes, transcripts, or enzymes of a community) to elucidate causal associations with biotransformations. [16][17][18][19][20] The general strategy is to isolate and characterize aggregate DNA, RNA, or proteins from in situ environmental communities and use the abundances of genes or gene products to establish associations that reflect the communities' potential for biotransforming one or more contaminants (referred to here as a meta-omics association study). In this context, we use the term "association" to refer to a statistical relationship between two variables, which may be described quantitatively (e.g., a linear or monotonic relationship) or qualitatively (e.g., a co-occurrence relationship).…”
Section: Why Use Meta-omics Association Studies?mentioning
confidence: 99%
“…A key parameter for cometabolic transformation of TOrCs is the availability of biodegradable DOC (BDOC) as primary substrate, both with respect to its quality and quantity 1,9 . Previous studies revealed that both the composition and the concentration of BDOC affect the total amount of biomass and the structure of the microbial community [10][11][12] as well as their functionality 13 and, therefore, 56 TOrCs removal 9 . It is well established that the transformation of TOrCs is enhanced under 57 carbon-limited conditions 3,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that both the composition and the concentration of BDOC affect the total amount of biomass and the structure of the microbial community [10][11][12] as well as their functionality 13 and, therefore, 56 TOrCs removal 9 . It is well established that the transformation of TOrCs is enhanced under 57 carbon-limited conditions 3,13,14 . Primary substrate comprised of refractory organic compounds, 58 such as humic acid like organic matter, led to an increased TOrCs removal compared to systems using a high fraction of easily degradable compounds like peptone/yeast 9,13 .…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of organic compounds can have a significant impact on redox-conditions in the subsoil. Furthermore, POC and DOC can be competitive substrates for OMP removal [12]. Still, DOC removal is a desired effect for BF and SAT.…”
Section: Introductionmentioning
confidence: 99%